YIELD ANALYSIS OF MAIZE VARIETIES IN VARIED AGRO-ECOLOGIES OF SOUTHWESTERN NIGERIA - OLOYEDE-KAMIYO, Q. O.; ADETUMBI, J. A.; OLASOJI, J. O.; AMUSAN, I. S. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
There is a gap between yield potential of maize varieties and the realized yield on farmers’ field in South Western Nigeria. There is need to reduce this yield disparity to boost farmers’ productivity. A study was conducted at three outstations of the Institute of Agricultural Research and Training, covering three agro-ecological zones of Nigeria to determine the extent of the yield gap in maize varieties and possible solutions. Four maize varieties- BR9943DMRSR-W, BR9928DMRSR-Y, SUWAN 1-SR and ART/98/SW6-OB were evaluated at Ilora, Kishi and Orin-Ekiti between 2013-2017. Each variety was planted to one hectare and repeated three times. Data were collected on yield, seed yield, percentage seed yield and percentage yield gap. Data were subjected to analysis of variance. Means were separated using Duncan Multiple Range Test (DMRT). Mean squares of variety, location, year and their interactions were significant for all the traits. Variety BR9928DMRSR had the highest mean yield (1.35t/ha), seed yield (1.25t/ha) with the least yield gap (39.9%). The highest mean yield was recorded at Orin-Ekiti, while the least yield and highest yield gap were recorded at Kishi. The highest yield was obtained in 2016 and the least in 2015. ART/98/SW6-OB and BR9928DMRSR-Y performed best at Orin-Ekiti. This study revealed that the yield potentials of most maize varieties according to breeders’ presentations are not realized in South Western Nigeria. Hence, effort towards non-limiting management such as good soil management, adequate soil moisture through irrigation, optimum plant population density and timely management practices throughout the crop growth cycle should be intensified.